Seletividade dos extratos aquosos e alcoólicos de Calotropis procera (Aiton, 1811) (Gentianales: Apocynaceae) sobre Euborellia annulipes (Lucas, 1847) (Dermaptera: Anisolabididae) - Oliveira Filho, Manoel Cícero de (2022)
The use of plant extracts for pest control has been gaining ground in recent years, mainly because it is harmless to humans and does not leave residues in food. Thus, some plants such as silk cotton (Calotropis procera) are being studied because they have insecticidal potential. The application of plant extracts in crops to control insect pests can lead to the reduction of natural enemies, such as earwigs Euborellia annulipes, which are great allies of biological control. Thus, it is necessary to understand the action of these products on the biology of predatory insects. The objective of this research was to evaluate the influence of aqueous and alcoholic extracts of C. procera at different concentrations on the predatory insect E. annulipes. The research was carried out at the Laboratory of Invertebrate Zoology (LABIN) of the Department of Biosciences of the Center for Agricultural Sciences of the Federal University of Paraíba (CCA-UFPB), Campus II, Areia - PB, under controlled conditions (temperature: 25 ± 1 ºC; relative humidity: 70 ± 10%; photophase: 12 hours). The concentrations of 0, 5, 10, 15 and 20% of the aqueous and alcoholic extract of C. procera leaves were tested, with topical application on nymphs and adults of E. annulipes. Were evaluated insect survival, morphological and reproductive parameters. The mentioned concentrations were also applied on the eggs of the predatory insect to verify the ovicidal effect. Under laboratory conditions, the aqueous extract of C. procera is harmless to the predator E. annulipes, in topical application; the alcoholic extract of C. procera proves to be harmless in the concentration of 5%, and little harmful in the concentration of 10, 15 and 20% to the predatory insect. Furthermore, when applied on E. annulipes eggs, with increasing extract concentration, there is a reduction in egg viability, and this reduction is greater when the alcoholic extract is used.